1982
DOI: 10.1007/bf02535097
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of 3‐oxo triterpenes in the unsaponifiable matter of some vegetable fats

Abstract: Fourteen vegetable oils were examined and 3‐oxo triterpenes are present in the unsaponifiable matter of shea (Butyrospermum parkii), illipe (Shorea stenoptera), mango kernel (Mangifera indica), kokum (Garcinia indica) and phulwara (Madhuca butyracea) fats but not in cocoa butter, dhupa fat (Vateria indica), soybean, peanut, mustard, corn, palm, coconut or mowrah (Madhuca latifolia) fats.Lipids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…95–108, 5.68 g). Residue C was rechromatographed over silica gel to give a triterpene fraction, which was subjected to HPLC (ODS, 95% MeOH) to afford compounds 1 (1.38 mg) and 9 (1.12 mg) [16]. Residue D was rechromatographed over silica gel to give a triterpene fraction, which was subjected to HPLC (ODS, 95 % MeOH) to afford compounds 2 (1.60 mg), 3 (2.40 mg), 5 (1.61 mg) [17], 8 (1.39 mg) [18], and 10 (2.82 mg) [19].…”
Section: Methodsmentioning
confidence: 99%
“…95–108, 5.68 g). Residue C was rechromatographed over silica gel to give a triterpene fraction, which was subjected to HPLC (ODS, 95% MeOH) to afford compounds 1 (1.38 mg) and 9 (1.12 mg) [16]. Residue D was rechromatographed over silica gel to give a triterpene fraction, which was subjected to HPLC (ODS, 95 % MeOH) to afford compounds 2 (1.60 mg), 3 (2.40 mg), 5 (1.61 mg) [17], 8 (1.39 mg) [18], and 10 (2.82 mg) [19].…”
Section: Methodsmentioning
confidence: 99%
“…Kolhe et al [50] reported that 3-oxo triterpenes are not present in peanut oil, being the practical significance of this fact that oxo triterpenes could be used to detect contamination with other oils or fats.…”
Section: Methylsterols and Triterpenic Alcoholsmentioning
confidence: 97%
“…The NSF of avocado oil was prepared by the method of Kolhe et al (1982) with modifications. The avocado oil (25 g) in ethanol/water (3:1 v/v, 100 mL) and KOH (17.5 g) was refluxed for 2-4 h, till the completion of saponification, followed by dilution with water and extraction of NSF with n-hexane.…”
Section: Extraction Of Nonsaponifiable Fraction Of Avocado Oilmentioning
confidence: 99%